2014
DOI: 10.3892/br.2014.296
|View full text |Cite
|
Sign up to set email alerts
|

Association of NQO1 and TNF polymorphisms with Parkinson’s disease: A meta-analysis of 15 genetic association studies

Abstract: Abstract. Parkinson's disease (PD) is a neurodegenerative movement d'isorder that affects ~2% of the population aged ≥65 years. NAD(P)H-quinone oxidoreductase 1 (NQO1) and tumor necrosis factor-α (TNF-α) are two important factors in the generation of oxidative stress in PD. The aim of the present study was to assess the association of NQO1 and tumor necrosis factor (TNF) polymorphisms with PD. A meta-analysis was performed that included data from 15 studies comprising 2,858 patients and 2,907 healthy controls.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…In this study, we evaluated the effect of selected SNPs from inflammation and oxidative stress pathways on the risk for PD and AEs occurrence due to dopaminergic treatment of PD. Several studies evaluating the effect of genetic polymorphisms or alterations in proteins’ functions in the inflammation- and oxidative stress-related pathways on the PD risk and pathogenesis have already been performed [31, 32, 3439]. However, no studies evaluating genetic variability in these pathways affecting the occurrence of AEs of dopaminergic treatment have been conducted to date.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, we evaluated the effect of selected SNPs from inflammation and oxidative stress pathways on the risk for PD and AEs occurrence due to dopaminergic treatment of PD. Several studies evaluating the effect of genetic polymorphisms or alterations in proteins’ functions in the inflammation- and oxidative stress-related pathways on the PD risk and pathogenesis have already been performed [31, 32, 3439]. However, no studies evaluating genetic variability in these pathways affecting the occurrence of AEs of dopaminergic treatment have been conducted to date.…”
Section: Discussionmentioning
confidence: 99%
“…Also TNF-α rs1800629 has been associated with the disease risk [31], but later studies did not confirm the result [32, 33]. Moreover, two other TNF-α SNPs [34, 35] and IL6 rs1800795 [36] showed the same association. Bridge between inflammatory processes and ROS/RNS stress may be presented by NOS1 .…”
Section: Introductionmentioning
confidence: 99%
“…The role of TNFα -1031 T/C and -308 G/A (rs1800629) in PD was previously evaluated [22,23]. Here, we evaluated two additional TNFα polymorphisms; (TNFα -863 C/A and TNFα -857 C/T) [8,38].…”
Section: Resultsmentioning
confidence: 99%
“…To date, it is unclear whether these polymorphisms correlate with PD development and progression, as several studies are equivocal in this regard. Previous meta-analyses have been investigated associations between inflammation and PD risk [1,22,23]; however, these studies focused on cytokine polymorphisms, rather than chemokines and their receptors. Therefore, we provide an updated comprehensive meta-analysis, summarizing the latest studies evaluating associations between inflammation-related gene polymorphisms and PD.…”
Section: Introductionmentioning
confidence: 99%
“…The genetic factors SIPA1L2, INPP5F, MIR4697, GCH1, VPS13C and DDRGK1 are involved in the onset of PD [10]. In a recent meta-analysis studies reported that TNF-1031 polymorphism is a possible risk factor for PD [11]. The roles of the genes parkin, DJ-1, PINK-1 and LRRK2 are not clear in the progression of PD [12].…”
Section: Editorialmentioning
confidence: 99%